Zoonoses and the Aboriginal and Torres Strait Islander population: A One Health scoping review. - Tamara Riley; Neil E Anderson; Raymond Lovett; Anna Meredith; Bonny Cumming (Public Library of Science (PLoS), 2022)
With limited access to animal health services, and high disease burdens among domesticated animals, Aboriginal and Torres Strait Islander communities in Australia face higher risk of disease including zoonoses. However, we lack understanding of the contribution of often preventable zoonoses to the health of these communities, which would enable us to enhance public health strategies and improve health outcomes. We conducted a scoping review to identify the current state of evidence on zoonoses in the Aboriginal and Torres Strait Islander population. We examined the size, scope and characteristics of the evidence base and analysed the zoonoses detected in the studies within a One Health framework. We identified 18 studies that detected 22 zoonotic pathogens in animals, people, and the environment, with most studies detecting pathogens in a single One Health sector and no studies investigating pathogens in all three sectors. Findings indicate that despite the strong conceptual foundations of One Health throughout the evidence base, evidence is lacking in application of this concept. There is a need to undertake further research that prioritises Aboriginal and Torres Strait Islander leadership, considers the contribution of human, animal and environmental health factors, and investigates the prevalence and impact of zoonoses in communities through a One Health approach.